Dead seas (2022) ebook - Scott, Cavan (Dead Seas (2022), 2023)
The New York Times-bestselling author of Star Wars: The High Republic – The Rising Storm turns to comics for this gruesome graphic novel takedown of the prison industrial complex—where the ghosts are real, dangerous, and incredibly valuable. Ghosts are real and dangerous. But they’re also valuable, their ectoplasm capable of curing countless diseases. There’s only one problem: Harvesting the wonder drug can be just as deadly. Prisoner Gus Ortiz is willing to take the risk in return for a reduced sentence—anything to see his daughter again. All it will take is a few months at sea scraping ectoplasm off the walls of the Perdition, a floating prison containing the most vicious ghosts on Earth. Surrounded by dark waters, Gus soon realizes that angry spirits are the least of his worries. Lock yourself away and set sail for this daring adventure by New York Times-bestselling author Cavan Scott (Star Wars: The High Republic) and fan-favorite artist Nick Brokenshire (Star Wars Adventures).